Balinsky's Darwinian roots - B. Fabian (South African Journal of Science, 2010)
Boris Ivan Balinsky (1905 - 1997) was Professor and Head of the Department of Zoology at the University of the Witwatersrand (Wits),Johannesburg,South Africa. He came to Wits in 1949 (via Munich and Edinburgh)from Kiev,where he was Professor of Embryology. As an acclaimed experimental embryologist he was especially famous for inducing a supernumerary limb in a newt when he was a19-year-old student in Ivan Schmalhausen's laboratory in Kiev 1924. In Johannesburg he wrote his famous text book of embryology, which influenced generations of students around the world.In addition to pioneering the application of electronmicros-copy to the study of early development, he tackled a variety of projects of general zoological interest. Lesser known is his latter daywork, carried out during his retirement, on variation and hereditability (especially of wing colouration)in the butterfly Acraeahorta, on which he published five papers from 1974 to 1986. His butterfly work showing the loose connection between the genotype and phenotype, with the genotype expressing itself in a variable way in the face of a constant physical environment,is of special interest in the current era of evolutionary and ecological developmental biology. His exposure to the stimulating evolutionary ideas of Schmalhausen during his early Kiev years no doubt provided a context for his butterfly work.Some ideas about how the 'loose connection between the genotype and phenotype'maybe achieved through behavioral modification or positional information during development are addressed in this paper in the light of recent work.In his eighties Balinsky worked on the classification of microlepidoptera on which he published several papers. He died in September 1997, just short of his 92nd birthday.